Science and Society: Scientific Societies in Victorian England - Pál, Eszter (Szociológiai Szemle, 2023)
The article analyzes the development of scientific thinking and production in England from the early to the late Victorian period. 19th century England saw a thorough change in every sphere of society including that of science. This was a time when the very idea of science – as understood in the 20th century – started to emerge. The article compares the modus operandi of three scientific bodies of utmost importance: the Royal Society, the British Association for the Advancement of Science, and the so-called X-Club. The first one represented an old-fashioned scientific body with a narrow, aristocratic social basis, whereas the BAAS, a reformist, much newer society was founded with the manifest idea of science as a universal, all-encompassing and neutral field, free of political and religious influences. The article shows that despite this official standing, the BAAS still represented a narrow range of scientific, political, cultural and social interests. In contrast to both of these bodies, the X-Club, an informal but highly influential set of nine scientists, introduced the idea of a modernized science. Largely due to their influence and shrewd strategic action, by the end of the century the scientific sphere had become far more independent of extra-scientific influences than ever before. The article concludes, however, that this independence meant a greater need to disguise the social and cultural embeddedness of science with a new set of criteria for scientific legitimacy, rather than actual, full autonomy.